Preparation method of polylactic acid / carbon nanotube / graphene nanosheet composite material
By combining the Pickering emulsion template method and the melt blending method, the uniform dispersion of carbon nanotubes and graphene nanosheets in the PLA composite material is achieved, which solves the contradiction between conductive properties and mechanical properties, and significantly improves the overall performance of the material.
Patent Information
- Application Number
- CN202310475770.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-04-26
AI Technical Summary
While the existing conductive PLA composite materials improve the conductivity and electromagnetic shielding properties, the mechanical properties of the existing conductive PLA composite materials have decreased, and the dispersion of carbon-based fillers is insufficient, which affects the overall performance of the material.
By combining the Pickering emulsion template method and melt blending method, cellulose nanocrystals are used as dispersants and emulsion stabilizers for conductive fillers, uniform dispersion between carbon nanotubes and graphene nanosheets is achieved to form an excellent conductive network.
Under the low filling amount of conductive filler, the conductivity and electromagnetic shielding performance of composite materials are significantly improved, while maintaining good mechanical properties, and are suitable for electronic components and electromagnetic shielding fields.
Smart Images

Figure BDA0004205468240000091 
Figure HDA0004205468260000011 
Figure HDA0004205468260000012
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional polymer composite materials, and in particular to a method for preparing a polylactic acid / carbon nanotube / graphene nanosheet composite material. Background Art
[0002] With the rapid development of communication and electronic equipment, electromagnetic shielding pollution has become increasingly serious, seriously affecting the normal operation of instruments and equipment and people's health. To solve this problem, more and more people have begun to pay attention to conductive polymer composites. Compared with traditional metal electromagnetic shielding materials, conductive polymer composites have more advantages, such as light weight, high conductivity and good processing performance. Polylactic acid (PLA) is an environmentally friendly material with advantages such as high tensile strength, good biocompatibility, easy molding and processing, and biomass sources. Therefore, it has become one of the most promising biodegradable polymers. In addition, polylactic acid can also be filled with carbon-based conductive fillers such as carbon black (CB), carbon nanotubes (CNTs), carbon fibers (CF) or graphene nanosheets (GNPs) to prepare conductive polymer composites. This material not only has good conductivity, but also can effectively resist electromagnetic pollution. Therefore, conductive PLA composites have broad application prospects in electromagnetic shielding of electronic equipment and instruments.
[0003] Traditional conductive PLA composites are usually prepared by mixing conductive fillers with polymer matrices by solution blending, emulsion blending or melt blending. For example, patent CN105331062B discloses a method for preparing carbon nanotube / polylactic acid conductive composites by melt blending, and patent CN104629275A discloses a graphene / polylactic acid composite with high conductivity stability prepared by solution blending. In order to obtain PLA composites with high conductivity and high electromagnetic shielding performance, it is crucial to establish an interconnected conductive network in the polymer matrix. Some researchers (Wang Yafei, Preparation and Electromagnetic Shielding Performance of Polylactic Acid / Carbon Nanotube / Two-Dimensional Nanosheet Composites [D], Zhengzhou University, 2021) prepared CNTs / GNPs masterbatch containing PEO by solution blending-freeze drying, and melt blended it to prepare PLA / CNTs / GNPs composites. Although the composite has good conductivity and electromagnetic shielding properties, the filler dispersion is not significantly improved, and there is agglomeration, which seriously affects the mechanical properties of the composite itself.
[0004] At present, the main factors limiting the comprehensive performance of conductive PLA composites are the content of carbon fillers and their dispersibility in the polymer matrix. Since nano-scale conductive fillers are easily aggregated in viscous polymer melts, a high content of carbon fillers needs to be added to the polymer matrix to obtain excellent conductivity and electromagnetic shielding properties. However, a high content of fillers will lead to a decrease in the mechanical properties of the composite. Therefore, it is urgent to develop a more effective strategy to solve the dispersion problem of carbon fillers in the PLA matrix and reduce the amount of carbon fillers added to improve the comprehensive performance of conductive PLA composites.
[0005] The Pickering emulsion template method has been successfully used to prepare polymer-based composites with excellent carbon-based filler dispersibility. Cellulose derivatives, including cellulose nanofibers, cellulose nanocrystals (CNC) and regenerated cellulose (RC), have been used to prepare PLA / cellulose composites by the Pickering emulsion template method and can be used as emulsion stabilizers and dispersants. For example, patent CN115678162A discloses a method for preparing cellulose nanofiber / polypropylene composites by Pickering emulsion. Yu et al. (B. Yu, Z. Zhao, S. Fu, et al. Fabrication of PLA / CNC / CNT conductive composites for high electromagnetic interference shielding based on Pickering emulsions method [J]. Compos Part A-Appl S, 2019, 125, 105558) reported a PLA / CNT / CNC composite with an isolated CNT network structure using the Pickering emulsion template method, which has a high conductivity of 59.3S / m and an EMI SE of 41.8dB at 4.3wt% CNTs loading. However, the isolated structure still results in poor mechanical properties compared to pure PLA. Although the Pickering emulsion template method stabilized by cellulose derivatives can achieve high conductivity and electromagnetic shielding performance at a relatively low addition amount, the mechanical properties of the composite material still need to be improved. Therefore, it is necessary to invent a more effective method to promote the dispersion of carbon-based materials in the polymer matrix.
[0006] The present invention proposes a new preparation method to solve the contradiction between the conductivity and mechanical properties of polymer-based composite materials in the prior art. The method adopts a processing method combining the Pickering mold emulsion template method and the masterbatch melt blending to successfully prepare a PLA / CNTs / GNPs composite material. Compared with the prior art, the composite material exhibits excellent conductivity and electromagnetic shielding performance at a lower conductive filler filling amount while maintaining good mechanical properties. This provides an important solution for applications in the fields of electronic components, safety protection, etc. Summary of the invention
[0007] The purpose of the present invention is to provide a polylactic acid / carbon nanotube / graphene nanosheet composite material and a preparation method thereof. The prepared polylactic acid composite material can exhibit high electrical conductivity, high electromagnetic shielding performance and good mechanical properties at a low compound filler filling content. The preparation method is simple and easy to implement and is suitable for industrial production and application.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The present invention provides a method for preparing a polylactic acid / carbon nanotube / graphene nanosheet composite material, the method comprising the following steps:
[0010] S1: dissolving polylactic acid in dichloromethane to obtain an oil phase; uniformly dispersing cellulose nanocrystals, graphene nanosheets and carbon nanotubes in deionized water to obtain an aqueous phase; pouring the aqueous phase into the oil phase, and emulsifying at 8000-16000 rpm on a homogenizer for 1-5 min to obtain a PLA / CNTs / GNPs Pickering emulsion;
[0011] The volume of the dichloromethane is 8-12 mL / g (preferably 10 mL / g) based on the mass of the polylactic acid; the volume of the deionized water is 540-580 mL / g (preferably 562 mL / g) based on the mass of the cellulose nanocrystals; the mass ratio of the cellulose nanocrystals, the graphene nanosheets and the carbon nanotubes is 1-2:1-3:1 (preferably 1:1:1); the volume ratio of the dichloromethane to the deionized water is 1:2.5-3.5 (preferably 1:3.1);
[0012] In step S1, the emulsification is carried out at 8000-16000 rpm for 1-5 min. If the speed is too slow, the emulsification effect is not obvious, and the filler CNTs and GNPs cannot be well coated on the PLA surface; if the speed is too fast, the aspect ratio and surface morphology of the filler CNTs and GNPs will be destroyed, resulting in incompleteness of the filler. In one embodiment of the present invention, the emulsification is carried out at 12000 rpm for 3 min. Within the scope of the present invention, the emulsion can be successfully prepared.
[0013] S2: Stir the PLA / CNTs / GNPs Pickering emulsion described in step S1 at 300-700 rpm for 12-36 hours, filter after the dichloromethane solvent evaporates, and dry the filter cake to obtain a P-PLA / xCNTs / yGNPs powder masterbatch;
[0014] In step S2, the stirring blade speed is maintained at 300-700 rpm for 12-36 hours to volatilize the dichloromethane solvent. Too fast a speed will destroy the stability of the emulsion. P-PLA / xCNTs / yGNPs powder masterbatch: where P represents the Pickering emulsion template method, and x and y represent the mass fractions of CNTs and GNPs in the polymer, respectively.
[0015] S3: Melt-blending the P-PLA / xCNTs / yGNPs powder masterbatch described in step S2 with the polylactic acid powder to obtain the polylactic acid / carbon nanotube / graphene nanosheet composite material; the mass ratio of the P-PLA / xCNTs / yGNPs powder masterbatch to the polylactic acid powder is 1:0.43-9 (preferably 1:2.3).
[0016] Further, the polylactic acid (PLA) described in step S1 is polylactic acid 4032D, with a density of 1.24 g / cm 3 , melt index is 6.17g / cm 3 , melting point 160.9℃.
[0017] Furthermore, the cellulose nanocrystals (CNC) described in step S1 are added in the form of an aqueous dispersion of cellulose nanocrystals, the aqueous dispersion of cellulose nanocrystals having a solid content of 4.6%. The length of the cellulose nanocrystals is 200-800 nm, and the diameter is 1-20 nm.
[0018] Furthermore, the carbon nanotubes (CNTs) described in step S1 are carbon nanotubes NC7000, with an average diameter of 9.5 nm and an average length of 1.5 μm.
[0019] Furthermore, the graphene nanosheets (GNPs) described in step S1 are graphene nanosheets XF021, with a diameter of 5-10 μm and a thickness of 3-10 nm.
[0020] Further, the melt blending in step S3 is carried out in a Haake torque rheometer, and the melt blending conditions are 170-190°C, 30-80r / min, and melt blending for 5-10min. Preferably, the blending temperature is 180°C, the rotation speed is 60r / min, and the blending time is 8min.
[0021] Compared with the prior art, the beneficial effect of the present invention is that: the present invention discloses a method for preparing a polylactic acid-based composite material by combining a Pickering emulsion template method and melt blending to improve filler dispersion. Among them, the amphiphilic CNC is used as a dispersant and emulsion stabilizer for CNTs and GNPs. The present invention first realizes the uniform dispersion of one-dimensional CNTs and two-dimensional GNPs conductive fillers in the aqueous phase through the amphiphilicity of CNC, and then blends the PLA dissolved in the oil phase with the CNC, one-dimensional CNTs and two-dimensional GNPs conductive fillers uniformly dispersed in the aqueous phase by the Pickering emulsion template method, and then filters and dries it to obtain a P-PLA / CNTs / GNPs particle masterbatch. The obtained P-PLA / CNTs / GNPs particle masterbatch is melt blended with a PLA material to finally obtain a PM-PLA / CNTs / GNPs composite material with good dispersion effect.
[0022] This method improves the dispersion effect of filler CNTs and GNPs in the PLA matrix and forms many uniform and stable conductive pathways inside the PLA material matrix, so that a PLA-based composite material with significantly improved conductivity and electromagnetic shielding properties can be obtained at a lower filler content. The composite material also maintains good mechanical properties and can be widely used in electronic components, electromagnetic shielding, safety protection and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is the electrical conductivity of PM-PLA / xCNTs / yGNPs composites with different mass fractions of CNTs and GNPs;
[0024] Figure 2 It is the electromagnetic shielding of PM-PLA / xCNTs / yGNPs composites with different mass fractions of CNTs and GNPs;
[0025] Figure 3 It is the mechanical curve of PM-PLA / xCNTs / yGNPs composites with different mass fractions of CNTs and GNPs. DETAILED DESCRIPTION
[0026] The technical scheme of the present invention is further specifically described below through specific embodiments and in conjunction with the accompanying drawings. In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry, and all raw materials and composite materials of the embodiments are vacuum dried under the same conditions. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0027] Example 1
[0028] 18g of polylactic acid (PLA) powder (4032D, produced by Nature Works, USA) was dissolved in 180ml of dichloromethane solvent and stirred vigorously at room temperature to prepare a PLA solution as an oil phase. 21.74g of a cellulose nanocrystal (CNC) suspension (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.) with a solid content of 4.6%, 1g of graphene nanosheets (GNPs) (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 1g of carbon nanotubes (CNTs) (NC7000, produced by Nanocyl, Belgium) were poured into 540ml of ionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of CNTs and GNPs. The aqueous solution containing CNC, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified on a homogenizer at a speed of 12000 rpm for 3 minutes to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500 rpm for 24 hours to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch. The filler content of the obtained P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch was diluted to 0.1 of the original: 5g of P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch and 45g of PLA powder were added to the Haake torque rheometer, the blending temperature was 180°C, the speed was 60r / min, and the blending time was 8min. Finally, the PM-PLA / 0.48CNTs / 0.48GNsP composite material was obtained after blending and dilution. Subsequently, the PM-PLA / 0.48CNTs / 0.48GNPs composite material was measured using a four-probe, vector network analyzer and electronic universal testing machine, and the results are as follows Figure 1 , 2 , 3 and Table 1.
[0029] Example 2
[0030] 18g PLA powder (4032D, produced by Nature Works, USA) was dissolved in 180ml dichloromethane solvent and stirred vigorously at room temperature to prepare PLA solution as oil phase. 21.74g CNC suspension with a solid content of 4.6% (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.), 1g GNPs (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 1g CNTs (NC7000, produced by Belgium Nanocyl Co., Ltd.) were poured into 540ml deionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of GNPs and CNTs. The aqueous solution containing CNC, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified on a homogenizer at a speed of 12000 rpm for 3 minutes to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500 rpm for 24 hours to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch; the filler content of the obtained P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch was diluted to the original 0.3. 15g P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch and 35g PLA powder were added to the Haake torque rheometer, the blending temperature was 180℃, the speed was 60r / min, and the blending time was 8min. Finally, the PM-PLA / 1.43CNTs / 1.43GNPs composite material was obtained after blending and dilution. Then the PM-PLA / 1.43CNTs / 1.43GNPs composite material was measured using a four-probe, vector network analyzer and electronic universal testing machine. The results are as follows Figure 1 , 2 , 3 and Table 1.
[0031] Example 3
[0032] 18g PLA powder (4032D, produced by Nature Works, USA) was dissolved in 180ml dichloromethane solvent and stirred vigorously at room temperature to prepare PLA solution as oil phase. 21.74g CNC suspension with a solid content of 4.6% (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.), 1g GNPs (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 1g CNTs (NC7000, produced by Belgium Nanocyl Co., Ltd.) were poured into 540ml deionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of GNPs and CNTs. The aqueous solution containing CNC, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified at a speed of 12000 rpm for 3 minutes on a homogenizer to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500 rpm for 24 hours to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch; the filler content of the obtained P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch was diluted to the original 0.5. 25g of P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch and 25g of PLA powder were added to the Haake torque rheometer, the blending temperature was 180℃, the speed was 60r / min, and the blending time was 8min. Finally, the PM-PLA / 2.38CNTs / 2.38GNPs composite material was obtained after blending and dilution. Subsequently, the PM-PLA / 2.38CNTs / 2.38GNPs composite material was measured using a four-probe, vector network analyzer, and electronic universal testing machine. The results are as follows Figure 1 , 2 , 3 and Table 1.
[0033] Example 4
[0034] 18g PLA powder (4032D, produced by Nature Works, USA) was dissolved in 180ml dichloromethane solvent and stirred vigorously at room temperature to prepare PLA solution as oil phase. 21.74g CNC suspension with a solid content of 4.6% (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.), 1g GNPs (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 1g CNTs (NC7000, produced by Belgium Nanocyl Co., Ltd.) were poured into 540ml deionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of GNPs and CNTs. The aqueous solution containing CNC, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified at a speed of 12000rpm for 3min on a homogenizer to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500rpm for 24h to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch; the filler content of the obtained P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch was diluted to the original 0.7. 35g P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch and 15g PLA powder were added to the Haake torque rheometer, the blending temperature was 180℃, the speed was 60r / min, and the blending time was 8min. Finally, the PM-PLA / 3.33CNTs / 3.33GNPs composite material was obtained after blending and dilution. Then the PM-PLA / 3.33CNTs / 3.33GNPs composite material was measured using a four-probe, vector network analyzer and electronic universal testing machine. The results are as follows Figure 1 , 2 , 3 and Table 1.
[0035] Comparative Example 1
[0036] 50g PLA powder (4032D, produced by Nature Works, USA) was added to the Haake torque rheometer, the blending temperature was 180°C, the speed was 60r / min, and the blending time was 8min. Finally, the PLA material after blending and dilution was obtained. Subsequently, the PLA material was measured using a four-probe, a vector network analyzer, and an electronic universal testing machine, and the results are shown in Table 1.
[0037] Comparative Example 2
[0038] 50.25g PLA powder (4032D, produced by Nature Works, USA), 17.44g CNC suspension with a solid content of 4.6% (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.), 0.75g GNPs (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 0.75g CNTs (NC7000, produced by Belgium Nanocyl Co., Ltd.) were added to the Haake torque rheometer, the blending temperature was 180°C, the speed was 60r / min, and the blending time was 8min. Finally, the M-PLA / 1.43CNTs / 1.43GNPs composite material after blending and dilution was obtained. Subsequently, the M-PLA / 1.43CNTs / 1.43GNPs composite material was measured using a four-probe, vector network analyzer and electronic universal testing machine, and the results are shown in Table 1.
[0039] Comparative Example 3
[0040] 16.75g PLA powder (4032D, produced by Nature Works, USA) was dissolved in 167.5ml dichloromethane solvent and stirred vigorously at room temperature to prepare PLA solution as oil phase. 5.81g CNC suspension with a solid content of 4.6% (produced by Zhejiang Jinjiahao Green Nanomaterial Co., Ltd.), 0.25g GNPs (XF021, produced by Nanjing Xianfeng Nano Co., Ltd.) and 0.28g CNTs (NC7000, produced by Belgium Nanocyl Co., Ltd.) were poured into 502.5ml ionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of GNPs and CNTs. The aqueous solution containing CNC, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified at a speed of 12000rpm for 3min on a homogenizer to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500rpm for 24h to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 1.43CNTs / 1.43GNPs composite material. Subsequently, the P-PLA / 1.43CNTs / 1.43GNPs composite material was measured using a four-probe, a vector network analyzer and an electronic universal testing machine, and the results are shown in Table 1.
[0041] Comparative Example 4
[0042] 18g PLA powder (4032D, produced by Nature Works, USA) was dissolved in 180ml dichloromethane solvent and stirred vigorously at room temperature to prepare PLA solution as oil phase. 21.74g cellulose nanofiber (CNF) suspension with a solid content of 4.6% (produced by Zhejiang Hanghua New Material Technology Co., Ltd.), 1g GNPs (XF021, produced by Nanjing Xianfeng Nano Company) and 1g CNTs (NC7000, produced by Belgium Nanocyl Company) were poured into 540ml deionized water and ultrasonically treated for 30min at room temperature with a power of 30W to achieve uniform dispersion of GNPs and CNTs. The aqueous solution containing CNF, CNTs and GNPs was poured into the PLA solution (oil phase) as the aqueous phase for mixing, and then emulsified at a speed of 12000 rpm for 3 minutes on a homogenizer to prepare a PLA / CNTs / GNPs Pickering emulsion; the obtained PLA / CNTs / GNPs Pickering emulsion was maintained at a stirring paddle speed of 500 rpm for 24 hours to volatilize the dichloromethane solvent. After the dichloromethane solvent evaporated, the precipitated microspheres were filtered and dried to obtain a P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch; the filler content of the obtained P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch was diluted to the original 0.3. 15g P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch and 35g PLA powder were added to the Haake torque rheometer, the blending temperature was 180℃, the speed was 60r / min, and the blending time was 8min. Finally, the PM-PLA / 1.43CNTs / 1.43GNPs composite material was obtained after blending and dilution. Subsequently, the PM-PLA / 1.43CNTs / 1.43GNPs composite material was measured using a four-probe, vector network analyzer and electronic universal testing machine, and the results are shown in Table 1.
[0043] Table 1
[0044]
[0045] Depend on Figure 1As can be seen from Table 1, it is the conductivity dot diagram of PM-PLA / xCNTs / yGNPs composite material, M-PLA / 1.43CNTs / 1.43GNPs composite material and P-PLA / 1.43CNTs / 1.43GNPs composite material after PLA melt blending and at different dilution levels of P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch (Examples 1 to 4 and Comparative Examples 1 to 4). The conductivity of the PM-PLA / xCNTs / yGNPs composite material prepared by the preparation method of the present invention with CNC as the dispersant increases with the increase of GNPs and CNTs content. Among them, the conductivity of the PM-PLA / 0.48CNTs / 0.48GNP composite material is 0.6S / m, which is 3.0×10 higher than that of pure PLA. 13 times; the conductivity of PM-PLA / 1.43CNTs / 1.43GNPs composite material is 43.5S / m, which is 2.2.×10 higher than that of pure PLA. 15 times; the conductivity of PM-PLA / 2.38CNTs / 2.38GNPs composite material is 91.7S / m, which is 4.6.×10 higher than that of pure PLA. 15 times; the conductivity of PM-PLA / 3.33CNTs / 3.33GNPs composite material is 178.6S / m, which is 8.9.×10 higher than that of pure PLA. 15 times. In comparison, the conductivity of the M-PLA / 1.43CNTs / 1.43GNPs composite material is 33.3S / m, the conductivity of the M-PLA / 1.43CNTs / 1.43GNPs composite material is 38.6S / m, and the conductivity of the PM-PLA / 1.43CNTs / 1.43GNPs composite material prepared by using CNF as a dispersant is 40.1S / m. It is obvious that the conductivity of the M-PLA / 1.43CNTs / 1.43GNPs composite material, the P-PLA / 1.43CNTs / 1.43GNPs composite material and the PM-PLA / 1.43CNTs / 1.43GNPs prepared by Comparative Examples 2, 3 and 4 are much lower than that of the PM-PLA / 1.43CNTs / 1.43GNPs composite material. In general, the PLA-based composites prepared using this method have higher electrical conductivity and have obvious advantages over dual-filler direct Pickering emulsion template blending, direct melt blending and other dispersant preparations.
[0046] Depend on Figure 2It can be seen that the electromagnetic shielding values of PM-PLA / xCNTs / yGNPs composites, M-PLA / 1.43CNTs / 1.43GNPs composites and P-PLA / 1.43CNTs / 1.43GNPs composites in the X-band after PLA melt blending and at different dilution levels of P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch (Examples 1 to 4 and Comparative Examples 1 to 4) are shown. The electromagnetic shielding of the PM-PLA / xCNTs / yGNPs composite material with CNC as the dispersant prepared by the preparation method of the present invention increases with the increase of GNPs and CNTs content. Among them, the electromagnetic shielding value of PM-PLA / 0.48CNTs / 0.48GNPs composite material is 8.0dB, which is 7.7dB higher than that of pure PLA; the electromagnetic shielding value of PM-PLA / 1.43CNTs / 1.43GNPs composite material is 20.1dB, which is 19.8dB higher than that of pure PLA; the electromagnetic shielding value of PM-PLA / 2.38CNTs / 2.38GNPs composite material is 22.1dB, which is 21.8dB higher than that of pure PLA; the electromagnetic shielding value of PM-PLA / 3.33CNTs / 3.33GNPs composite material is 26.1dB, which is 25.8dB higher than that of pure PLA. As a comparison, the electromagnetic shielding of the M-PLA / 1.43CNTs / 1.43GNPs composite material is 18.3dB, the electromagnetic shielding of the P-PLA / 1.43CNTs / 1.43GNPs composite material is 16.7dB, and the electromagnetic shielding of the PM-PLA / 1.43CNTs / 1.43GNPs composite material prepared by using CNF as a dispersant is 18.5dB. It is obvious that the electromagnetic shielding of the M-PLA / 1.43CNTs / 1.43GNPs composite material and the P-PLA / 1.43CNTs / 1.43GNPs composite material prepared by comparative examples 2, 3 and 4 and the PM-PLA / 1.43CNTs / 1.43GNPs prepared by CNF are much lower than the electromagnetic shielding of the PM-PLA / 1.43CNTs / 1.43GNPs composite material. In general, the PLA-based composite material prepared by this method has a higher electromagnetic shielding, especially the PN 1.43 C 1.43 G 1.43 The electromagnetic shielding value of the composite material is 20.1dB, which meets the commercial standard and has obvious advantages over dual-filler direct Pickering emulsion template blending, direct melt blending and other dispersant preparations.
[0047] Depend on Figure 3It can be seen that the tensile curves of PM-PLA / xCNTs / yGNPs composites, M-PLA / 1.43CNTs / 1.43GNPs composites and P-PLA / 1.43CNTs / 1.43GNPs composites after PLA melt blending and at different dilution levels of P-PLA / 4.8CNTs / 4.8GNPs powder masterbatch (Examples 1 to 4 and Comparative Examples 1 to 4) are shown. The tensile properties of the PM-PLA / xCNTs / yGNPs composites prepared by the preparation method of the present invention with the dispersant being CNC slowly decrease with the increase of the content of GNPs and CNTs, but the composites still maintain good mechanical properties. Among them, the tensile strength of PM-PLA / 0.48CNTs / 0.48GNPs composite material is 58.4MPa, which is 8.3MPa lower than that of pure PLA, but its Young's modulus is 27.8% higher than that of pure PLA; the tensile strength of PM-PLA / 1.43CNTs / 1.43GNPs composite material is 56.2MPa, which is 10.5MPa lower than that of pure PLA, but its Young's modulus is 42.3% higher than that of pure PLA. %; the tensile strength of PM-PLA / 2.38CNTs / 2.38GNPs composite material is 53MPa, which is 13.4MPa lower than that of pure PLA, but its Young's modulus is 51.0% higher than that of pure PLA; the tensile strength of PM-PLA / 3.33CNTs / 3.33GNPs composite material is 52.1MPa, which is 14.6MPa lower than that of pure PLA, but its Young's modulus is 64.2% higher than that of pure PLA. In comparison, the tensile strength of the M-PLA / 1.43CNTs / 1.43GNPs composite material is 50.3 MPa, the tensile strength of the P-PLA / 1.43CNTs / 1.43GNPs composite material is 40.7 MPa, and the tensile strength of the PM-PLA / 1.43CNTs / 1.43GNPs composite material prepared using CNF as a dispersant is 51.2 MPa. It is obvious that the tensile strengths of the M-PLA / 1.43CNTs / 1.43GNPs composite material, P-PLA / 1.43CNTs / 1.43GNPs composite material prepared in Comparative Examples 2 and 3 and the PM-PLA / 1.43CNTs / 1.43GNPs prepared with CNF are all much lower than the tensile strength of the PM-PLA / 1.43CNTs / 1.43GNPs composite material. In general, the PLA-based composites prepared using this method can maintain good mechanical properties and have obvious advantages over dual-filler direct Pickering emulsion template blending, direct melt blending and other dispersant preparations.
[0048] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a polylactic acid / carbon nanotube / graphene nanosheet composite material, characterized in that The method comprises the following steps: S1: dissolving polylactic acid in dichloromethane to obtain an oil phase; uniformly dispersing cellulose nanocrystals, graphene nanosheets and carbon nanotubes in deionized water to obtain an aqueous phase; pouring the aqueous phase into the oil phase, and emulsifying on a homogenizer at 8000-16000 rpm for 1-5 min to obtain a PLA / CNTs / GNPs Pickering emulsion; The volume of the dichloromethane is 8-12 mL / g based on the mass of the polylactic acid; the volume of the deionized water is 540-580 mL / g based on the mass of the cellulose nanocrystals; the mass ratio of the cellulose nanocrystals, graphene nanosheets and carbon nanotubes is 1-2:1-3:1; the volume ratio of the dichloromethane to the deionized water is 1:2.5-3.5; S2: Stir the PLA / CNTs / GNPs Pickering emulsion described in step S1 at 300-700 rpm for 12-36 h, and after the dichloromethane solvent evaporates, filter and dry the filter cake to obtain P-PLA / x CNTs / y GNPs powder masterbatch; where P represents Pickering emulsion template method, x and y represent the mass fractions of CNTs and GNPs in the polymer, respectively; S3: P-PLA / x CNTs / y The GNPs powder masterbatch is melt-blended with the polylactic acid powder to obtain the polylactic acid / carbon nanotube / graphene nanosheet composite material; the P-PLA / x CNTs / y The mass ratio of GNPs powder masterbatch to polylactic acid powder is 1:0.43-9.
2. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The polylactic acid described in step S1 is polylactic acid 4032D.
3. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The cellulose nanocrystals in step S1 are added in the form of an aqueous dispersion of cellulose nanocrystals, and the solid content of the aqueous dispersion of cellulose nanocrystals is 4.6%.
4. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The cellulose nanocrystals in step S1 have a length of 200-800 nm and a diameter of 1-20 nm.
5. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The carbon nanotubes described in step S1 are carbon nanotubes NC7000.
6. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The graphene nanosheets described in step S1 are graphene nanosheets XF021.
7. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The volume of the dichloromethane in step S1 is 10 mL / g based on the mass of the polylactic acid.
8. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The volume of the deionized water in step S1 is 562 mL / g based on the mass of the cellulose nanocrystals.
9. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The volume ratio of the dichloromethane to the deionized water in step S1 is 1:3.
1.
10. The method for preparing the polylactic acid / carbon nanotube / graphene nanosheet composite material according to claim 1, characterized in that: The melt blending in step S3 is carried out in a Haake torque rheometer, and the melt blending conditions are 170-190° C., 30-80 r / min, and melt blending for 5-10 min.
Citation Information
Patent Citations
Preparation method of high-conductive-stability graphene composite material
CN104629275A
A carbon nanotube / polylactic acid conductive composite material and its preparation method
CN105331062B
Preparation method of carbon nano tube (CNT) / polylactic acid (PLA) electromagnetic shielding composite material with isolation structure
CN105038160A
Antibacterial magnetic composite for 3D printing
CN106009574A